An Asparagine-Rich Protein Nbnrp1 Modulate Verticillium dahliae Protein PevD1-Induced Cell Death and Disease Resistance in Nicotiana benthamiana - Liang, Yingbo; Cui, Shichun; Tang, Xiaoli; Zhang, Yi; Qiu, Dewen; Zeng, Hongmei; Guo, Lihua; Yuan, Jingjing; Yang, Xiufen (Frontiers in Plant Science, 2018)
PevD1 is a fungal protein secreted by Verticillium dahliae. Our previous researches showed that this protein could induce hypersensitive responses-like necrosis and systemic acquired resistance (SAR) in cotton and tobacco. To understand immune activation mechanisms whereby PevD1 elicits defense response, the yeast two-hybrid (Y2H) assay was performed to explore interacting protein of PevD1 in Arabidopsis thaliana, and a partner AtNRP (At5g42050) was identified. Here, AtNRP homolog in Nicotiana benthamiana was identified and designated as Nbnrp1. The Nbnrp1 could interact with PevD1 via Y2H and bimolecular fluorescence complementation (BiFC) analyses. Moreover, truncated protein binding assays demonstrated that the C-terminal 132 amino acid (development and cell death, DCD domain) of Nbnrp1 is required for PevD1-Nbnrp1 interaction. To further investigate the roles of Nbnrp1 in PevD1-induced defense response, Nbnrp1-overexpressing and Nbnrp1-silence transgenic plants were generated. The overexpression of Nbnrp1 conferred enhancement of PevD1-induced necrosis activity and disease resistance against tobacco mosaic virus (TMV), bacterial pathogen Pseudomonas syringae pv. tabaci and fungal pathogen V. dahliae. By contrast, Nbnrp1-silence lines displayed attenuated defense response compared with the wild-type. It is the first report that an asparagine-rich protein Nbnrp1 positively regulated V. dahliae secretory protein PevD1-induced cell death response and disease resistance in N. benthamiana.